Perlindungan Hukum Terhadap Penelantaran Anak Secara Ekonomi di Kabupaten Sukabumi - Muhamad Salman Farisi; R. Eriska Ginalita Dwi Putri (Majelis: Jurnal Hukum Indonesia, 2025)
Economic neglect of children is a condition where a child does not receive sufficient basic needs fulfillment from parents or caregivers, either intentionally or due to inability. This research aims to examine and analyze the mechanisms and barriers in providing legal protection for economically neglected children in Sukabumi District. This study employs normative legal research with data sources consisting of interviews, observations, and literature studies. The method used to process and analyze the data is qualitative analysis, conducted at the Integrated Service Center for Women and Children Empowerment (P2TP2A) in Sukabumi District. According to the research findings, the forms of legal protection provided include supervision, prevention, care, and rehabilitation. The barriers in providing legal protection for economically neglected children include funding issues, lack of understanding of procedures among personnel, reluctance of society to report cases, absence of clear Standard Operating Procedures (SOPs), overlapping roles and responsibilities, and lack of empathy.